Impact of different heating duration on water content in ore samples: analysis, regression insights, and implications for sustainable energy sources - Utami, Hermin Hardyanti; Nensi, Ariskawati; Pratiwi, Hermin Lutfiah Mita (Jurnal Kimia Fullerene, 2024)
This study investigates the impact of heating duration on the water content of five different ore samples (ore_A, ore_B, ore_C, ore_D, ore_E) using a systematic experimental approach and advanced data analysis techniques. The ore samples were homogenized and subjected to heating at 105°C for durations of 2, 4, 6, and 8 hours. Water content was determined gravimetrically, with the data showing that water content generally increased with heating time. For example, ore_A's water content rose from 22.00% ± 7.94 after 2 hours to 40.00% ± 7.94 after 8 hours, while ore_B's water content increased from 6.50% ± 10.54 to 29.00% ± 10.54 over the same period. Statistical analyses, including Shapiro-Wilk normality tests, ANOVA (F-statistic = 4.706, p-value = 0.0116), and Tukey's HSD post-hoc tests, revealed significant differences in water content among certain ore samples. Linear regression analysis showed a strong relationship between heating duration and water content, with R-squared values ranging from 0.83 (ore_A) to 0.99 (ore_D), confirming the robustness of the model. These findings provide valuable insights into the thermal properties of ores, with implications for optimizing processing conditions in ore treatment.